2022
DOI: 10.1093/omcr/omac048
|View full text |Cite
|
Sign up to set email alerts
|

Acute pyelonephritis revealing a rare renal collision tumor of papillary and chromophobe cell carcinoma with sarcomatoid features

Abstract: A 59-year-old male patient was admitted to the emergency room with febrile right flank pain. The computed tomography scan and the magnetic resonance imaging had objectified lesion image occupying the upper half of the right kidney, measuring 82 mm, suggesting an infectious origin without excluding the infected tumor. He was put under antibiotics. A percutaneous biopsy revealed renal cell carcinoma with suppurative tumor necrosis. He underwent a right radical nephrectomy. The histopathological study revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“… 11 Also, Boukhannous et al reported a unilateral RCC masquerading as pyelonephritis. 3 Like Boukhannous et al, our patient had unilateral papillary RCC presenting with features of pyelonephritis. Our management was focused on obstructive pyelonephritis.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“… 11 Also, Boukhannous et al reported a unilateral RCC masquerading as pyelonephritis. 3 Like Boukhannous et al, our patient had unilateral papillary RCC presenting with features of pyelonephritis. Our management was focused on obstructive pyelonephritis.…”
Section: Discussionsupporting
confidence: 62%
“…reported a unilateral RCC masquerading as pyelonephritis 3. Like Boukhannous et al, our patient had unilateral papillary RCC presenting with features of pyelonephritis.…”
supporting
confidence: 68%
See 3 more Smart Citations